The expression of glucanase encoding gene (CaβGlu)in chili (Capsicum annuum L.) as a response to Fusarium oxysporum infection - Yunnia Rahmandanni; Sri Pujiyanto; Rejeki Siti Ferniah (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2019)
Indonesia is a tropical country with highest level of biodiversity, especially in the agricultural sector. Chili (Capsicum annumm. L) is a very well-known and widely used agricultural product in the world, which makes chili becomes one of the most considerable national product. The chili production is oftentimes very susceptible to some diseases caused by virus, fungi, or bacteria. One of the most common diseases in chili cultivation is Fusarium wilt, which is caused by Fusarium oxysporum. This disease can cause a major loss and up to 50% crop failure. Many procedures have been done to find the best cultivar with a resistance trait to Fusarium oxysporum, including by observing and testing the chili’s genetic resistance. One of the resistance genes in chili is β -1, 3- glucanase-encoding gene, which produces an enzyme to hydrolize the cell wall of pathogenic fungi. This research aimed to determine the expression of the glucanase-encoding gene (CaβGlu) in chili as a response to Fusarium oxysporum infection. The methods including chili cultivation, F. oxysporum inoculation, isolation of chili leaves RNA, glucanase-encoding gene expression analysis used qRT-PCR, and data analysis. The result of CaβGlu gene expression is higher than the control in the first 6 hours after inoculation, and decreasing in the 48th and 96th hours. The conclusion was the infection of Fusarium oxysporum is activating the expression of CaβGlu gene which was expressed best in the first 6 hours after inoculation.